Bisoprolol in cardiovascular disease treatment - S. N. Tolpygina; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
Literature data are presented on the role of beta-adrenoblockers (BAB) and bisoprolol, in particular, in the treatment of cardiovascular disease (CVD), including coronary heart disease (CHD), chronic heart failure, arterial hypertension (AH) and cardiac arrhythmias. The main clinical trials, proving beneficial survival effects of BAB in CVD patients, are briefly described. The authors present the results of their original comparative pharmaco-economic study on clinical equivalence of original and generic bisoprolol in AH treatment. Original medication was more effective than generic one, with similar tolerability of both bisoprolol forms.